ANALISIS PENETAPAN PENGADILAN AGAMA LAMONGAN NO: 70/PDT.P/PA.LMG. TENTANG DISPENSASI KAWIN - Alanshori, M. Zainuddin (Akademika, 2017)
This study aims to answer the questions of what is the consideration of judges in the Lamongan Religious Court on the establishment of marriage dispensation on the grounds of being able to give so-called nafkah (feed) and what is the perspective of Islamic Law and Marriage Law in Indonesia against the establishment of Lamongan Religious Court judges about marriage dispensation on the grounds to be able to give nafkah. In order to answer the above questions, the writer used data collection techniques through documentation and interviews by using descriptive analysis with deductive mindset. The study concludes that the judge stipulating the dispensation of marriage on the grounds of being able to give nafkah is based on the fulfillment of the conditions of marriage except the age requirement for the prospective grooms having not reached the age of 19 years, as meant in the Compilation of Islamic Law Article 15 paragraph 1: (1) "For the benefit of families and households, marriage shall only be carried out if the legal age of marriage as stipulated in Article 7 of Law No.1 year 1974 namely the groom is at least 19 years old and the bride is at least 16 years old". Then supported by some written evidence as well as witnesses, the decision of Lamongan Religious Court in the establishment of marriage dispensation is very relevant to Islamic Law and Law no. 1 of 1974. Although, basically in its legal considerations, the judges are less concerned about the skills of the groom. Thus, such establishment has no implications for the validity of marriage, since in fiqh it is permissible as long as there is no element of fraud or any party to be harmed by the marriage.